α-Acetolactate synthase of Lactococcus lactis contributes to pH homeostasis in acid stress conditions - Zuljan, Federico Alberto (2014)
Lactic Acid Bacteria (LAB) are recognized as safe microorganisms with the capacity to improve the quality of dairy products. When the LAB Lactococcus lactis is employed as starter for the production of fermented foods, high quantities of important aroma compounds such as diacetyl are generated by means of the diacetyl/acetoin pathway. Our previous results obtained with L. lactis strains report that this pathway is activated under acidic conditions. In this study, we describe the metabolism of pyruvate, a diacetyl/acetoin precursor, and its contribution to pH homeostasis in this microorganism. L lactis strain IL1403 is able to cometabolize pyruvate and glucose at low pH, producing lactate, acetate as well as diacetyl/acetoin compounds. In contrast, the als defective strain, which is incapable of producing C4 compounds, appeared sensitive to pyruvate under acidic conditions rendering it unable to grow. Accordingly, the als-mutant strain showed a simultaneous inability to alkalinize internal and external media. These results demonstrate that the decarboxylation reactions associated to the diacetyl/acetoin pathway represent a competitive advantage in a condition of intracellular pyruvate accumulation during growth at low pH. Interestingly, a genomic comparative analysis shows that this pathway has been conserved in L. lactis during the domestication of different strains. Also, our analysis shows that the recent acquisition of the cit cluster required for citrate metabolism, which contributes to diacetyl/acetoin production as well, is the specific feature of the biovar. diacetylactis. In this regard, we present for first time genetic evidence supporting the proposal made by Passerini et al. (2013) who postulated that the expression "biovar. citrate" should be more appropriate to define this specific industrial strain.